Neotethyan Subduction Ignited the Iran Arc and Backarc Differently. Issue 5 (1st May 2020) - Shafaii Moghadam, H.; Li, Q. L.; Li, X. H.; Stern, R. J.; Levresse, G.; Santos, J. F.; Lopez Martinez, M.; Ducea, M. N.; Ghorbani, G.; Hassannezhad, A.
Abstract: Most arcs show systematic temporal and spatial variations in magmatism with clear shifts in igneous rock compositions between those of the magmatic front (MF) and those in the backarc (BA). It is unclear if similar magmatic polarity is seen for extensional continental arcs. Herein, we use geochemical and isotopic characteristics coupled with zircon U‐Pb geochronology to identify the different magmatic style of the Iran convergent margin, an extensional system that evolved over 100 Myr. Our new and compiled U‐Pb ages indicate that major magmatic episodes for the NE Iran BA occurred at 110–80, 75–50, 50–35, 35–20, and 15–10 Ma. In contrast to NE Iran BA magmatic episodes, compiled data from MF display two main magmatic episodes at 95–75 and 55–5 Ma, indicating more continuous magmatism for the MF than for the BA. We show that Paleogene Iran serves as a useful example of a continental arc under extension. Our data also suggest that there is not a clear relationship between the subduction velocity of Neotethyan Ocean beneath Iran and magmatic activity in Iran. Our results imply that the isotopic compositions of Iran BA igneous rocks do not directly correspond to the changes in tectonic processes or geodynamics, but other parameters such as the composition of lithosphere and melt source(s) should be considered. In addition, changes in subduction zone dynamics and contractional versus extensional tectonic regimes influenced the composition of MF and BA magmatic rocks. These controls diminished the geochemical and isotopic variations between the magmatic front and backarc. Plain Language Summary: Most arcs show systematic temporal and spatial variations in magmatism with a clear shift in the composition of igneous products between those of the magmatic front and those in the backarc (BA). Our U‐Pb ages for the NE Iran BA identify five magmatic episodes for the NE Iran backarc, which occurred at 110–80 million years ago (Ma), 75–50, 50–35, 35–20, and 15–10 Ma. The 110–80 Ma magmatic episode was a time of strong regional extension due to subduction initiation along the Zagros suture zone, while the younger episodes reflect maturation of the magmatic arc. The first magmatic episode is represented by magmas dominated by inputs from the underlying mantle, as does the next episode (75–50 Ma). The third pulse (50–35 Ma) shows increasing contributions from the underlying crust. The fourth magmatic pulse occurred at 35–20 Ma, and the volume of these magmas was less than other magmatic pulses. The final pulse in the NE Iran BA (15–10 Ma) suggests that there was a change in magmatic architecture beneath the BA. Magmatic pulses at 110–80 and 50–35 Ma accompanied extension, while others accompanied compression due to collision with Arabia. Contribution of continental crust components was highest for the 50–35 Ma magmatic episode. Key Points: Late Mesozoic‐Cenozoic active continental margin in Iran was characterized by vigorous magmatism in magmatic front and backarc Iran back‐arc flare‐up occurred in two pulses at 110–80 and 50–35 Ma., while other pulses at 75–50, 35–20, and 15–10 Ma show magmatic lulls In contract to NE Iran BA magmatic episodes, the magmatic front indicates a continuous magmatism from 95 to 5 Ma